Development of multi-epitope vaccines against the monkeypox virus based on envelope proteins using immunoinformatics approaches - Tan, Caixia; Zhu, Fei; Pan, Pinhua; Wu, Anhua; Li, Chunhui (Frontiers in Immunology, 2023)
Monkeypox virus (MPXV) is a member of the Orthopoxvirus genus of the Poxviridae family that causes a disease in humans with symptoms similar, but less severe, to smallpox. Since May 2022, cases of monkeypox have been increasingly reported worldwide. There are, however, no proven therapy or vaccines available for monkeypox, although prior studies have demonstrated that the smallpox vaccine was capable of offering some degree of protection against monkeypox, its practical efficacy still needs to be tested. In this study, several multi-epitope vaccines were designed with the help of immunoinformatics approaches. Three target proteins, A35R and B6R, enveloped virion (EV) form-derived antigens, and H3L, expressed on the mature virion (MV) form, were selected for epitope identification as their functions of mediating cell-to-cell viral spread and facilitating virus binding to host cells. After screening, a total of 7 cytotoxic T lymphocyte (CTL) epitopes, 6 helper T lymphocyte epitopes and 6 linear B-cell epitopes were selected for vaccine construction. Five vaccine constructs (MPXV-1–5) were created by fusing shortlisted epitopes with appropriate adjuvants and linkers. Based on various immunological, physiochemical and structural parameters, MPXV-2 and MPXV-5 were selected for further analysis. The secondary and three-dimensional (3D) structures of selected vaccines were predicted by PSIPRED 4.0 and Robetta servers, respectively. Refinement and quality verification of 3D structures of MPXV-2 and MPXV-5 were also performed. Molecular docking and molecular dynamics (MD) simulations were run to understand the binding pattern and binding affinity of the vaccines with Toll-like receptors (TLRs) and major histocompatibility complexes (MHCs) molecules, and the results of them showed that the MPXV-2 and MPXV-5 had a stronger affinity to TLRs (TLR2, TLR4) and MHCs. In addition, immune stimulation, population coverage, codons optimization and in silico cloning were also performed on MPXV-2 and MPXV-5. These findings suggested that the MPXV-2 and MPXV-5 had high potency against MPXV, but further studies are required to validate their safety and efficacy.